A Low Level of Darunavir Resistance–Associated Mutation Emergence in Patients With Virological Failure During Long-term Use of Darunavir in People With HIV. The ANRS CO3 Aquitaine Cohort. (19th November 2020) - Chaussade, Hélène; Tumiotto, Camille; Le Marec, Fabien; Leleux, Olivier; Lefèvre, Lucile; Lazaro, Estibaliz; Lafon, Marie-Edith; Nyamankolly, Elsa; Duffau, Pierre; Neau, Didier; Bellecave, Pantxika; Bonnet, Fabrice
Abstract: Background: Ritonavir-boosted darunavir (DRV/r) is a protease inhibitor (PI) indicated for the treatment of naïve and pretreated HIV-infected patients since 2007. Our study aims to describe DRV/r-treated patients experiencing virological failure (VF) documented with HIV resistance testing. Methods: Data from patients belonging to the ANRS CO3 Aquitaine Cohort treated with a regimen including DRV/r between February 2007 and December 2015 were analyzed. Baseline characteristics of patients experiencing VF (defined by 2 consecutive plasma viral loads >50 copies/mL) were compared with those without VF. We then described factors associated with VF as emergence of IAS DRV resistance–associated mutations (RAMs). Results: Among the 1458 patients treated at least once with a DRV/r-based regimen, 270 (18.5%) patients experienced VF during follow-up, including 240 with at least 1 genotype resistance test (GRT). DRV RAMs were detected in 29 patients (12%). Among them, 25/29 patients had ≥2 DRV RAMs before DRV/r initiation, all of whom had experienced VF during previous PI treatments. For 18/29, DRV/r was maintained after VF, and controlled viremia was restored after modification of DRV-associated antiretroviral molecules or increased DRV dose. Finally, only 6/29 patients selected new DRV RAMs after DRV/r initiation. All of these experienced previous VFs while on other PIs. Conclusions: These results highlight the efficacy and robustness of DRV/r, as the emergence of DRV RAMs appeared in <0.4% of patients receiving a DRV/r-based regimen in our large cohort. Abstract : A low level of darunavir resistance-associated mutation emergence in patients with virological failure during long term use of boosted darunavir. Confirmation of the robustness of this protease inhibitor in the ANRS CO3 Aquitaine cohort in a real life setting.